'Topos' and Utopia in Evgenios Voulgaris' Life and Work (1716-1806) - Carras, Iannis C. (The Historical Review/La Revue Historique, 2005)
One of the central figures of the Enlightenment in the Greek world, Evgenios Voulgaris (1716-1806) has been criticised for becoming increasingly reactionary in later years. This article argues that an understanding of the importance of place and movement in Voulgaris' world -as also in his world-view- helps explain elements of continuity and change in his writings more generally. Rather than a shift from enlightenment to reaction, the article depicts a slow progression from an early Voulgaris intent -both in his writings and in the Athos Academy- on fusing Orthodoxy and Enlightenment, to a later Voulgaris less intent on creating a rational system out of the many influences on his thought and more insistent on the creation of a place for the Graikoi, liberated from the Ottomans. The complex inter-relation between the geographic, political and social conditions and the thought processes of one particular individual are examined. Given these conditions, and bearing in mind the dangers of a crude geographic determinism, Voulgaris' attempts to reconcile, indeed create a rational system out of the many influences on his thought, present considerable interest but were inevitably unlikely to succeed.